Hematological testing for blood doping in sports (2001)
The EPO Epidemic in Sport (Hein Vergruggen) Hematology Parameters: Usefulness and Limitations in Monitoring Red Cell Production (Giuseppe d'Onofrio) Erythropoietin, Iron and Red Blood Cell Production: Laboratory Evaluation (Carlo Brugnara) Red Cell Parameters in Winter Endurance Sports (James Stray-Gundersen) The Development of a Blood Test for EPO Abuse (Robin Parisotto and Mike Ashenden) Source: Bloodline Reviews